Bioinspired strategy to tune viscoelastic response of thermoplastic polyisoprene by retarding the dissociation of hydrogen bonding. (6th January 2021) - Tang, Maozhu; Xu, Ran; Zhang, Rong; Bai, Si-Jie; Huang, Guangsu; Xu, Yun-Xiang
Abstract: Hydrogen bonding as a commonly used dynamic crosslink in elastomers suffered from inefficient stability against elevated temperature or low tensile rate. Herein, a bioinspired strategy was developed to retard the dissociation process, therefore resulting in mechanically strong and stable thermoplastic polyisoprene. Specifically, penta-alanine groups pendant on polyisoprene assemble into β-sheets and serve as crosslinkers, which usually are unstable and disassemble at moderate temperature or low tensile rate. In this work the addition of Ca 2+ ions will destroy partial β-sheet structures, but at the same time coordinate with peptide aggregates and retard the dissociative process of hydrogen bonding against either the increase of temperature or stretching speed in a controlled manner. Stress relaxation test showed that the activation energies for viscous flow and relaxation time below 127 °C are obviously increased after the addition of Ca 2+ ions. The mechanism study showed that the well mixing of calcium salt and peptide phase in polyisoprene matrix is critical for the formation of coordination interactions, which manipulate the dissociation of peptide aggregates. This strategy represents a feasible approach to tune the viscoelastic response of elastomers in a wide range. Graphical abstract: Image 1 Highlights: The thermostability and robustness of thermoplastic polyisoprene were improved. The dissociation process of hydrogen bonding aggregates was retarded. The coordination interactions between calcium ions and penta-alanines were investigated.